Pengaruh Pelatihan Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada Hotel Xyz : The Effect of Training and Work Motivation on Employee Performance at Hotel Xyz - Kasih, Cika Sentosa; Lestari, Tri (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
- Employee performance is one of the key factors determining organizational success, especially in the hospitality industry where service quality is crucial. The phenomenon at Hotel XYZ indicates performance issues such as task delays, lack of initiative, and varying work enthusiasm. This study aims to analyze the effect of training and work motivation on employee performance at Hotel XYZ. The research employed a quantitative approach with a descriptive-verificative method. A sample of 120 respondents was obtained using simple random sampling from a population of 172 employees. Data were collected through Likert-scale questionnaires and processed using SPSS version 27. Validity and reliability tests confirmed that the research instruments were appropriate. Multiple linear regression analysis produced the equation Y = 12.314 + 0.421X1 + 0.538X2. The t-test results indicated that both training and work motivation have a positive and significant effect on employee performance individually. The F-test result confirmed a simultaneous significant effect. The coefficient of determination (R²) of 0.389 indicated that 38.9% of employee performance variation was explained by training and motivation, while 61.1% was influenced by other factors outside this research.